Influence of Automated Fiber Placement (AFP) Parameters over Permeability and Performance for Dry CF Laminates - Elena Rodríguez Senín; Mario Román Rodríguez; Cristian Builes Cárdenas; Maria Ivette Coto Moretti (Engineering Proceedings, 2025)
AFP process has the advantage of producing high-performance components and reducing the manufacturing time and defects introduced in the final material thanks to the highly automated process, compared with more traditional methods. Selecting inappropriate AFP process parameters can influence the permeability of the preforms being manufactured and the later mechanical performance of the final component. This paper reviews in detail the influence of the main AFP process parameters (deposition velocity, compaction force and temperature) over the adhesion properties between carbon fiber tapes. Later, three parameter combinations are selected to evaluate their influence over preform permeability and the mechanical performance of the composite after the resin injection process (RTM).